2003
DOI: 10.1086/379052
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Pole Caustic Model for High‐Energy Light Curves of Pulsars

Abstract: We present a new model of high-energy light curves from rotation-powered pulsars. The key ingredient of the model is the gap region (i.e., the region where particle acceleration is taking place and high-energy photons originate) that satisfies the following assumptions: (1) the gap region extends from each polar cap to the light cylinder; (2) the gap is thin and confined to the surface of last open magnetic-field lines; (3) photon emissivity is uniform within the gap region. The model light curves are dominate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
350
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(361 citation statements)
references
References 28 publications
11
350
0
Order By: Relevance
“…The value of P is especially low (P ∼ 2 %) within the phase intervals trailing both peaks. Dyks & Rudak (2003) suggested that the minima in polarization percentage P could naturally result from the caustic nature of the peaks: superposition of emission from different altitudes (ie. with different position angles), which produces the peaks, could ensure both the decrease in P and the fast swings of ψ.…”
Section: Polarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of P is especially low (P ∼ 2 %) within the phase intervals trailing both peaks. Dyks & Rudak (2003) suggested that the minima in polarization percentage P could naturally result from the caustic nature of the peaks: superposition of emission from different altitudes (ie. with different position angles), which produces the peaks, could ensure both the decrease in P and the fast swings of ψ.…”
Section: Polarizationmentioning
confidence: 99%
“…In Fig. 4 of Dyks & Rudak (2003) we chose α = 70 • and ζ obs = 61 • to reproduce the observed peak separation of ∼ 0.43 while keeping the difference α − ζ obs smaller than ∼ 10 • to ensure the close approach to the narrow radio beam centered at the dipole axis. Given the relatively weak sensitivity of the peak locations to α and ζ obs (eg.…”
Section: Static Shape Dipolementioning
confidence: 99%
“…The model also explains the flattening of the X-ray spectra at soft energies as a result of propagating particles being subject to synchrotron losses all along their trajectories. Using this model, we show how observations in gamma-rays can predict the detectability of the pulsar in X-rays, and viceversa.Curvature and synchrotron emission from particles accelerated in magnetospheric gaps or reconnection (see e.g., Cheng et al 1986a,b;Romani 1996;Zhang & Cheng 1997;Hirotani & Shibata 1999;Muslimov & Harding 2003;Dyks & Rudak 2003;Kalapotharakos et al 2012;Philippov & Spitkovsky 2017) has been thought to be behind non-thermal pulsations. However, a simplified, unifying interpretation of pulsar spectra is still lacking.…”
mentioning
confidence: 99%
“…Certainly, extra acceleration due to ρ = ρ GJ exists too. As demonstrated in Fig.3, a very large acceleration may exist near the last open field lines, which could be favorable for the high energy emission in the caustic model (Dyks & Rudak 2003). An outer gap may not be possible if particles can flow out freely either from the surface (for negligible binding energy) or from the pair-formation-front (for enough binding energy) of a charged pulsar.…”
Section: Emo Egjmentioning
confidence: 83%